Effect of Government Policies and Support for Poverty alleviation of SSEs Owners in Kano and Niger States, Nigeria (UNIZIK Journal of Marketing, 2024)
This study examined the effect of Government policies and support to poverty alleviation of SSEs owners in Kano and Niger States. Government(s) in Nigeria have refocused interest on poverty reduction via SSEs for two decades and this is quite long enough to assess its performance. Two null hypotheses were formulated in relation of government policies and government support to poverty alleviation. Relevant literature was conceptually and empirically reviewed and both vicious cycle of poverty and Keynesian theories were adopted. A population of 202 registered SSEs with employees of 10-50 were extracted from a secondary data using purposive sampling. A sample size of 172 SSEs was determined via Yamane Formula. Multiple regression was used to test the hypotheses via Statistical Package for Social Science (SPSS) version 23. Descriptive statistics was engaged to analyse the bio data of the respondents. The paper established that government policies (Beta value = .132 and p value = .235) and support packages (Beta value = -.207 and p value = .064) have not positively impacted on SSEs owners to alleviate their poverty level. It recommended for overhauling the existing policies and support packages through bottom-up approach to policy formulation and implementation in order meet the demands of the SSEs environment
Keywords: SSE; SSEs Owners; Government policies; Government Support; Poverty Alleviation